2016
DOI: 10.1002/anie.201605997
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Dimerization and Polymerization of a Janus Diradical To Produce Labile C−C Bonds and Large Chromic Effects

Abstract: Conducting polymers can be synthesized by irreversible diradical monomer polymerization. A reversible version of this reaction consisting of the formation/dissociation of σ-dimers and σ-polymers from a stable quinonoidal diradical precursor is described. The reaction reversibility is made by a quinonoidal molecule which changes its structure to an aromatic species by forming weak and long intermolecular C-C single bonds. The reaction provokes a giant chromic effect of about 2.5 eV. The two opposite but complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
1
39
0
4
Order By: Relevance
“…[72] Similard imerization aggregation has been recently revealed for series of viologen cations showing preference for p-stacking as opposedt os igma bond formation throughacombination of EPR, optical spectroscopy and DFT modeling. [73] Casado et al [74] have shown using Raman, UV/Vis, EPR, and NMR spectroscopies that certain tetracyanoquinonoidal oligothiophenes are aggregating as both pancake bonded and s-bonded dimers and oligomers. Okino et al [75] found that certain N-substituted dicyanomethyl radicals with extended conjugation dimerize both in solution and in the crystal phase.…”
Section: Evidence Of Pancake Bonding In the Solution Phasementioning
confidence: 99%
“…[72] Similard imerization aggregation has been recently revealed for series of viologen cations showing preference for p-stacking as opposedt os igma bond formation throughacombination of EPR, optical spectroscopy and DFT modeling. [73] Casado et al [74] have shown using Raman, UV/Vis, EPR, and NMR spectroscopies that certain tetracyanoquinonoidal oligothiophenes are aggregating as both pancake bonded and s-bonded dimers and oligomers. Okino et al [75] found that certain N-substituted dicyanomethyl radicals with extended conjugation dimerize both in solution and in the crystal phase.…”
Section: Evidence Of Pancake Bonding In the Solution Phasementioning
confidence: 99%
“…[5a] For 2 2 six s-dimer configurations were also found, each with two s-bonds. [5,6] (See the Supporting Informationf or ad etailed basis set evaluation and further comments on alternative DFT calculations. This situation might, in principle,l ead to the formation of dimers and oligomers.F or 3 2 ,h owever, the staggered p-bonded dimer is the most stable configuration and is lower by 5.5 kcal mol À1 compared to the s-dimer configuration containing three Table 1: only 1 2 (stag), 2 2 (ecl) at 3 , 3 2 (ecl), 4 2 (ecl), and 5 2 (ecl) are presented because they have the best SOMO overlap, with intermolecular distances shorter or at ca.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…For p radicals, s-dimerization is Figure 1. [5] In the case of phenalenyl (1)itturns out that a s-dimer of 1 2 is more stable than the p-dimer by only 1.6 kcal mol À1 . The singly occupied p molecularorbital (SOMO) of 1 is illustrated on the top right.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This interesting interchange between the σ‐ and π‐dimer isomers is not limited to PLY derivatives. A diradical quinonoid oligothiophene has been synthesized which showed π‐, σ‐dimerization and polymerization . Another example is provided by the dimerization behavior of amine‐substituted dicyanomethyl radicals which can be switched from σ‐ to π‐dimerization as a function of substituents .…”
Section: Introductionmentioning
confidence: 99%